The effect of rare earth elements corrosion inhibitors on the corrosion of titanium & aluminium in chloride containing media - Manjo, Julius Mbimbi-Ikoli (My University, 2022)
Titanium and aluminium both showed good resistance to corrosion in both the saline NaCl and acidic HCl chloride containing solutions. This is due to their ability to form a passive protective, self-regenerating metal oxide layer. Titanium samples showed greater corrosion resistance by two orders of magnitude compared to the aluminium samples in NaCl, HCl solutions with and without inhibitors. The corrosion inhibitors used were lanthanum and cerium acetylacetone and these showed good corrosion inhibition effects, consistent through the weight loss tests and potentiodynamic scans. This was observed by examination through scanning electron microscopy and optical microscopy. The presence of inhibitors was observed to decrease the corrosion rate by one order of magnitude, when compared to the corrosion rate of corrosive media without inhibitor. The weight loss tests revealed that pitting occurred as a result of chloride attack on both aluminium and titanium, especially after immersion for a period of six weeks. Deep surface cracks were observed throughout the aluminium samples and to a smaller degree on the titanium samples. Lanthanum acetylacetone showed signs of acting as an anodic inhibitor in most of the potentiodynamic tests, by increasing Ecorr and shifting it towards a more positive (anodic) direction. However, cerium acetylacetone did not significantly and consistently show shifts in Ecorr, hence it was classified as a mixed inhibitor in this study for Al in NaCl and HCl systems.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Chemical Engineering, Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2022